Ghosts of Beirut [videorecording (DVD)] - Isaacharoff, Avi; Raz, Lior (Showtime, 2023)
Four-part limited series based on one of the most extraordinary real-life espionage stories of our time: the manhunt for Imad Mughniyeh, the elusive terrorist mastermind who outwitted his adversaries for over two decades. Based on a true story, Mugniyeh took terrorism to deadly new levels, creating public martyrs out of anonymous suicide bombers. As CIA and Mossad operatives were haunted by Imad's actions, they unexpectedly join forces in a high-stakes international chase to finally find and take down the man known as "the ghost."